2020
DOI: 10.1016/j.jclinepi.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Changing predictor measurement procedures affected the performance of prediction models in clinical examples

Abstract: Objectives: The aim of this study was to quantify the impact of predictor measurement heterogeneity on prediction model performance. Predictor measurement heterogeneity refers to variation in the measurement of predictor(s) between the derivation of a prediction model and its validation or application. It arises, for instance, when predictors are measured using different measurement instruments or protocols. Study Design and Setting: We examined the effects of various scenarios of predictor measurement heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Measurement heterogeneity refers to differences in the procedure and/or instruments used to measure the predictors. It has been shown that prognostic models including unreliable/misclassified predictors perform suboptimally on internal (271,272) and, especially, external validation (273)(274)(275). In prostate cancer, all standard variables used for developing prognostic models are known to be unreliably measured and/or are subject to measurement heterogeneity.…”
Section: Reliability and Measurement Heterogeneitymentioning
confidence: 99%
“…Measurement heterogeneity refers to differences in the procedure and/or instruments used to measure the predictors. It has been shown that prognostic models including unreliable/misclassified predictors perform suboptimally on internal (271,272) and, especially, external validation (273)(274)(275). In prostate cancer, all standard variables used for developing prognostic models are known to be unreliably measured and/or are subject to measurement heterogeneity.…”
Section: Reliability and Measurement Heterogeneitymentioning
confidence: 99%
“…The bottom graphs show effects on the absolute risk difference scale, which shows increasing benefits for higher-risk patients for both interventions. 23,38 Finally, use of trial or registry data cannot yield a model robust to missing values in the EHR database used for clinical prediction because the pattern of missingness present across research and EHR environments is expected to differ. The usual approaches addressing potential bias arising from missingness (eg, multiple imputation) are not designed to cope with missingness in variables used to generate predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has highlighted that heterogeneity in predictor measurement across different settings can substantially degrade model performance. 21,36 Finally, use of trial or registry data cannot yield a model robust to missing values in the EHR database used for clinical prediction, since the pattern of missingness present across research and EHR environments is expected to differ. The usual approaches addressing potential bias arising from missingness (e.g., multiple imputation) are not designed to cope with missingness in variables used to generate predictions.…”
Section: Discussionmentioning
confidence: 99%